2014
DOI: 10.1017/s1355770x14000552
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of improved air quality in urban Africa: a contingent valuation survey in Douala, Cameroon

Abstract: International audienceThis study investigates the effects of ‘time to think’ and ‘ballot box’ on willingness-to-pay, while providing the first empirical evidence on assessing the benefits of an air quality improvement program in urban Africa. Our hypothetical referendum scenario proposes to reduce the air pollution related morbidity rate in Douala, Cameroon by 25 per cent in exchange for a one-time surcharge on the electricity bill of each respondent. We find that on average WTP decreases by nearly one-fourth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Some studies showed significant influence, 61 while others were not able to confirm. 62,63 The amount of WTP of males was observed to be significantly higher than females in this paper. The reason might be that females are more sensitive than males about money.…”
Section: Resultssupporting
confidence: 46%
“…Some studies showed significant influence, 61 while others were not able to confirm. 62,63 The amount of WTP of males was observed to be significantly higher than females in this paper. The reason might be that females are more sensitive than males about money.…”
Section: Resultssupporting
confidence: 46%
“…First, studies that assessed people's additional WTP for electricity generated from NG-based CHP plant over coal-fired plant to mitigate air pollutants emissions remain scarce. Most of the related research has tackled public value for reducing the air pollutions or improving the air quality [17][18][19][20][21][22][23].…”
Section: Method: CVmentioning
confidence: 99%
“…In response to this concern, researchers had proposed to explicitly highlight the hypothetical problem in a script before respondents could make any decisions (cheap talk script) (Ami et al, 2011;Cummings & Taylor, 1999;Mahieu, 2010;Murphy et al, 2005b), remind the respondents that their decisions are consequential and could be used by policymakers about the provision of the public good or implementing the health policy (Bulte et al, 2005;Liu et al, 2010), give respondents time to think (Cook et al, 2011;Donfouet et al, 2015;Whittington et al, 1992), calibrating the respondents' answers using ex-post correction based on the certainty of respondents to the WTP questions (Blumenschein et al, 2008;Champ et al, 1997;Johannesson et al, 1999), and ask the respondents to make a commitment to tell the truth (oath script) (Jacquemet et al, 2013). In the current study, we explicitly used the oath script.…”
Section: Oath Scriptmentioning
confidence: 99%